On the metrological traceability and hierarchy of stable isotope reference materials aimed at realisation of the VPDB scale: Revision of the VPDB δ13C scale based on multipoint scale‐anchoring RMs. (24th February 2021) - Assonov, Sergey; Fajgelj, Ales; Allison, Colin; Gröning, Manfred
Abstract : Rationale: In recent years, the primary reference material (RM) for the VPDB scale, NBS19, has become unavailable, and the RM used for low‐end scale‐anchoring, LSVEC, was found unsuitable due a drift in the δ 13 C value. Given these problems, new RMs aimed at realising the VPDB δ 13 C scale with low uncertainty were produced. Establishing the consistency of the new RMs with the "old" RMs prompted our revision of the underlying principles of RM value assignments, and the VPDB δ 13 C scale realisation and its long‐term sustainability. Methods: Analysis of major developments of the VPDB scale, a review of the contemporary requirements for RMs, and comparison with well‐established measurement scales have been performed, with the aim of revising the VPDB δ 13 C scale, principles of RM value assignments, and calibrator hierarchy. Requirements for scale‐anchoring RMs with low uncertainty and measures to establish the scale sustainability have been formulated. Results: The revised scale realisation is based on multiple reference points, well‐defined calibration hierarchy and the use of well‐understood methods for value assignment. The realisation scheme includes the new primary RM IAEA‐603 and scale‐anchoring RMs IAEA‐610, IAEA‐611 and IAEA‐612, covering δ 13 C from +2.46 to −36.7 ‰ VPDB, with uncertainties, including inhomogeneity and stability assessment, of less than 0.015 ‰. The values of these four RMs were assigned in a mutually consistent way; agreement between measurements made using this realisation with those made using the VPDB scale of 2006 has been demonstrated on NIST CO2 RMs 8562–8564. Conclusions: Multipoint‐anchoring of the VPDB δ 13 C scale provides several distinct "points" on the scale as means for cross‐measurements to check the stability and viability of RMs and detect drift of values, if any. This ensures that the δ 13 C scale is suitable for the most demanding applications, and provides options for developing further RMs with high accuracy inside a robust scale realisation scheme.